Yield and quality of dry direct-seeded rice (Oryza sativa) as influenced by nitrogen and weed management practices in Eastern India - SINGH, SACHIN; GHOSH, A; DAS, T K; DHAR, SHIVA; TRIPATHY, SASMITA; PRASAD, S M (The Indian Journal of Agricultural Sciences, 2023)
Combined use of FYM and LCC based N management gave the highest grain yield, hulling, milling, head rice recovery, crude protein, protein yield (kg/ha) as well as highest nitrogen, phosphorus and potassium in grain and straw. In case of weed management practices, the sequential application of pendimethalin (1.5 kg/ha) as pre-emergence fb brown manuring with Sesbania aculeata (knocking down Sesbania by bispyribac-Na 25 g/ha at 25 DAS) resulted in better control of diverse weeds. It also proved to be the best treatment in terms of yield, physical and chemical grain quality parameters.